Comprehensive study of the antidiabetic drug metformin and its transformation product guanylurea in Greek wastewaters. (1st March 2015) - Kosma, Christina I.; Lambropoulou, Dimitra A.; Albanis, Triantafyllos A.
Abstract: Many pollutants such as pharmaceuticals and their transformation products (TPs) are not efficiently removed from wastewater treatment plants and enter into surface waters. The aim of this study was to investigate the occurrence and behavior of metformin, one of the most prescribed drugs worldwide, and its biological transformation product guanylurea, in eight wastewater treatment plants (WWTPs) of Greece. All WWTPs were equipped with conventional activated sludge treatment and the samples were taken from the influents and the effluents, over the four seasons of one year. The analytical method developed based on SPE followed by LC-UV/Vis-ESI/MS analysis, while positive findings were confirmed also by means of LTQ Orbitrap mass spectrometer. High polarity of both compounds led to the extraction with Oasis HLB and the use of the anionic surfactant SDS. The results showed that metformin dominated in the influents (bql-1167 ng/L), while guanylurea in the effluents (bql-627 ng/L) of the wastewater treatment plants, with Metformin/Guanylurea ratio ranging between 0.88 and 81.3 in the influents and between 0.005 and 0.78 in the effluents. Lack of a clear seasonal tendency in the occurrence and removal or formation was observed. Finally, an ecotoxicological risk assessment of metformin in effluent wastewaters took place by calculating the ratio between the environmental concentrations (MEC) and the predicted no effect concentrations (PNEC). Despite the fact that metformin presented low risk in all cases, an environmental concern is suspected for guanylurea since it is continuously released into the aquatic environment. Graphical abstract: Highlights: Comprehensive study of metformin and guanylurea in eight WWTPs in Greece. Further confirmation by means of LTQ Orbitrap MS. The Metformin/Guanylurea ratio appears to be variable. Concentration of guanylurea mostly exceeds its parent metformin in the effluents. Risk quotients for metformin were lower than 1.